2005
DOI: 10.1038/sj.bjc.6602703
|View full text |Cite
|
Sign up to set email alerts
|

Risk reduction of contralateral breast cancer and survival after contralateral prophylactic mastectomy in BRCA1 or BRCA2 mutation carriers

Abstract: The clinical outcome of contralateral prophylactic mastectomy (CPM) in women with a BRCA1 or BRCA2 mutation and a personal history of invasive breast cancer is unknown. We identified a cohort of 148 female BRCA1 or BRCA2 mutation carriers (115 and 33, respectively) who previously were treated for unilateral invasive breast cancer stages I -IIIa. In all, 79 women underwent a CPM, while the other women remained under intensive surveillance. The mean follow-up was 3.5 years and started at the time of CPM or at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
166
5
18

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(196 citation statements)
references
References 22 publications
7
166
5
18
Order By: Relevance
“…2 Contralateral prophylactic mastectomy (CPM) reduces the risk of breast cancer by 91-96%. 3,4 Although a significant improvement in survival has not been identified in most studies, a more recent study has demonstrated a modest survival benefit for women under 50. 5,6 Prophylactic mastectomy is usually reserved for patients who are at high risk for developing a contralateral breast cancer.…”
mentioning
confidence: 99%
“…2 Contralateral prophylactic mastectomy (CPM) reduces the risk of breast cancer by 91-96%. 3,4 Although a significant improvement in survival has not been identified in most studies, a more recent study has demonstrated a modest survival benefit for women under 50. 5,6 Prophylactic mastectomy is usually reserved for patients who are at high risk for developing a contralateral breast cancer.…”
mentioning
confidence: 99%
“…Some studies showed improved survival after CRRM, 14,17,[19][20][21] while others did not. 11,13,16,18 Also, previous studies often suffered from small sample sizes, 11,13,18 short follow-up 13,18,20 and heterogeneous study populations consisting of mixtures of sporadic, high-risk and BRCA-associated PBC patients. 16,18 In fact, only three studies exclusively reported on BRCA1/2 mutation carriers.…”
mentioning
confidence: 99%
“…16,18 In fact, only three studies exclusively reported on BRCA1/2 mutation carriers. 13,19,21 More knowledge on the efficacy of CRRM after BRCAassociated PBC is important as this allows for more accurate and tailored genetic and oncologic counselling for respective patients. In view of the limitations of previous studies, we designed a well-powered prospective study to establish the efficacy of CRRM after BRCA-associated PBC on overall survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who carry mutations in the BRCA genes may have more limited treatment options; their lifetime risk of recurrence in either the affected or unaffected breast is high enough that they benefit from double mastectomy [2]. Another group whose options may be limited comprises younger women, who tend to be diagnosed with later-stage disease because there is less routine screening of this population.…”
Section: Data On Treatmentmentioning
confidence: 99%